The Kingfisher book of planet earth - "Redfern, Martin" (Kingfisher Publications, London, 1999)
This volume offers an exploration of Planet Earth with comprehensive text and photographs. Travel back in time to the dramatic formation of our planet, go on a journey to the centre of the Earth, and find out how geology and the forces of nature continue to devastate and shape the surface.